Association of greenspace exposure with telomere length in preschool children. (November 2020) - Miri, Mohammad; de Prado-Bert, Paula; Alahabadi, Ahmad; Najafi, Moslem Lari; Rad, Abolfazl; Moslem, Alireza; Aval, Hamideh Ebrahimi; Ehrampoush, Mohammad Hassan; Bustamante, Mariona; Zare Sakhvidi, Mohammad Javad; Nawrot, Tim; Sunyer, Jordi; et al.
Abstract: Exposure to greenspace has been associated with a wide range of health benefits; however, the available evidence on the association of this exposure with telomere length (TL), an early marker of ageing, is still scarce. We investigated the association of greenspace exposure with TL in a sample of 200 preschool children (aged 5–7 years) residing in Sabzevar, Iran (2017). We comprehensively characterized different aspects of greenspace exposure encompassing residential, kindergarten, and total (including both residential and kindergarten) surrounding greenspace (using satellite-derived Normalized Difference Vegetation Index), residential and kindergarten distance to green spaces, time spent in private gardens and public green spaces, and the number of plant pots at home. Relative leukocyte TL (LTL) in blood samples of the study participants was measured using quantitative polymerase chain reaction (qPCR). We applied mixed effects linear regression models with kindergarten and qPCR plate as random effects, to estimate the association of indicators of greenspace exposure (one at a time) with LTL, controlled for relevant covariates. We observed an inverse association between distance from home and kindergarten to green spaces larger than 5000 m 2 and LTL. Moreover, higher total surrounding greenspace at 300m and 500m buffers and higher surrounding greenspace at 300m buffer around kindergarten and home were associated with longer LTL. Furthermore, longer time spent (h/week) in the public green spaces was associated with longer LTL. Our findings for residential and kindergarten distance to any green space (regardless of the size), residential surrounding greenspace at 100m and 500m buffers, kindergarten surrounding greenspace at 100m buffer, time spent in private gardens (h/week) and the number of plant pots at home were not conclusive. Our findings were generally suggestive for a positive association between greenspace exposure and LTL in preschool children. More studies are needed to confirm these findings in other settings with different climates and populations. Graphical abstract: Image 1 Highlights: Shorter leukocyte telomere length (LTL) is an indicator of biological ageing. We studied the association of greenspace exposure and LTL in preschool children. Higher distance to large green spaces was associated with shorter LTL. Higher residential surrounding greenspace was associated with longer LTL. Longer time spent in public green spaces was associated with longer LTL.